NiS1.97: a new efficient water oxidation catalyst for photoelectrochemical hydrogen generation - Bhosale, Reshma; Kelkar, Sarika A.; Parte, Golu; Fernandes, Rohan; Kothari, Dushyant; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2015)
NiS1.97, a sulfur-deficient dichalcogenide, in nanoscale form, is shown to be a unique and efficient photoelectrochemical (PEC) catalyst for H-2 generation by water splitting. Phase pure NiS1.97 nanomaterial is obtained by converting nickel oxide into sulfide by controlled sulfurization method, which is otherwise difficult to establish. The defect states (sulfur vacancies) in this material increase the carrier density and in turn lead to favorable band line-up with respect to redox potential of water, rendering it to be an effective photoelectrochemical catalyst. The material exhibits a remarkable PEC performance of 1.25 mA/cm(2) vs NHE at 0.68 V in neutral pH, which is almost 1000 times superior as compared with that of the stoichiometric phase of NiS2. The latter is well-known to be a cocatalyst but not as a primary PEC catalyst.
Keywords: dichlacogenide; Faradaic efficiency; Hydrogen generation; NiS1.97; nonstoichiometric; photoelectrochemical catalyst; sulfurization

Electrochemical performance of pre-lithiated ZnMoO4 and r-GO@ZnMoO4 composite anode for lithium-ion battery application - Bin Masood, Khalid; Parte, Golu; Jain, Neha; Dwivedi, Pravin K.; Kumar, Pushpendra; Shelke, V, Manjusha; Patel, Rp; Singh, Jai (Journal of the Taiwan Institute of Chemical Engineers, 2020)
Exploring a safer replacement of Li metal anode is crucial for technological, and fundamental importance. Li-metal is a preferred choice as anode material for lithium-ion battery (LIB) applications. However, parasitic dendritic growth on the Li metal surface during cycling causes instability and safety dreads. In the present study, we have investigated that the pre-lithiated ZnMoO4 is superior to its carbon-based counterparts (r-GO@ZnMoO4), moreover safer and sustainable than Li metal anode. The pre-lithiated ZnMoO4 delivers a better reversible capacity (similar to 1000 mAhg(-1) at 0.1 Ag-1), superior rate capability (similar to 400 mAh g(-1) at 2 Ag-1), and excellent cycling stability over 300 cycles at 0.1 Ag-1, as compared to bare ZnMoO4 and r-GO@ZnMoO4 composite. The present investigation is an attempt to provide a substitute for commonly used Li-metal/carbon anodes with better performance. (C) 2020 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Cycling stability; Electrochemistry; Li-ion battery; Nyquist plot; Rate performance; ZnMoO4 nanocomposites

High efficiency lithium storage in 3D composite foam of Co3O4 nanoparticles integrated carbon nanohorns - Dwivedi, Pravin K.; Parte, Golu; Thripuranthaka, M.; Shelke, Manjusha V. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2021)
A well-designed 3 dimensional (3D) nanocomposite foam of Co3O4 nanoparticles and functionalized carbon nano horns (CNH) is prepared by feasible wet chemistry followed by lyophilization. This 3D nanocomposite foam is evaluated electrochemically as anode material for lithium-ion battery (LIB). 3D hierarchical mesoporous hybrid of functionalized carbon nano horn-Co3O4 (CCO) shows excellent lithium storage properties with long cycle life due to high surface area, good conductivity, 3D interconnected mesoporous structure, mechanical and chemical stability and shortened diffusion path length for Li+ ions during lithiation-delithiation. The Co3O4 nanoparticles incorporated into interconnected CNH foam effectively increases the number of active sites of CCO nanocomposite and consequently increase in the reversible specific capacity and coulombic efficiency. Different compositions of CNH foam with Co3O4 nanoparticles are prepared, among which the CCO 1:1 foam displays reversible capacity of 797 mAhg1 at current density of 0.1 Ag-1 along with excellent rate performance. High specific capacity of around 702 mAhg(-1) is obtained even at the current density of 5 Ag-1.
Keywords: 3D CCO foam; carbon nanohorns; Excellent rate capability; Li ion diffusion coefficient; Long Cycle life

Sustainable composite of SnFe2O4 conversion alloying anode for lithium-ion storage - Yadav, Poonam; Parte, Golu; Malik, Wahid; Sabri, Ylias M.; Jones, Lathe A.; Shelke, V. Manjusha (Sustainable Energy & Fuels, 2022)
The development of high-performance, low-cost electrodes using sustainable materials for Li-ion batteries is of vital importance in view of their increasing demand for use in electronics and electric vehicles, as we transition from non-renewable energy resources. Challenges associated with commercial graphite anode materials include relatively low capacity, the use of high-temperature synthesis, Li dendrite formation, and limited rate capability. In this study, we present a tin ferrite SnFe2O4 (SFO) conversion alloying material (CAM), and its synergistic composite with a scalable and low-cost waste-derived carbon (WDC), which was prepared by low-temperature pyrolysis of a waste material sustainably. The combination of SFO with the WDC in the composite boosts the conductivity, diffusion kinetics, stability, and reversibility, and accommodates volume expansion upon cycling. The first charge capacity obtained for WDC, SFO, and SFO-WDC is 595, 1269, and 1331 mA h g(-1), respectively at 100 mA g(-1) in a Li-ion half-cell. In a full cell fabricated with LFP, a stable capacity of 80 mA h g(-1) at 100 mA g(-1) could be obtained, and the corresponding energy density for the SFO-WDCIILFP full cell is 300 W h kg(-1). Kinetic studies revealed that capacitance-controlled charge storage is dominant so the capacity was higher in the composite. This composite system addresses both the low capacity issue of the carbon anode and stability issues of CAMs while being compatible for use with current Li-ion battery technology.